Penggunaan Media Meronce Manik - Manik Untuk Melatih Kosentrasi Anak Autisme Di X - Nisa’ul Azizah; Fikri Yumna Aqila (CV. ITTC INDONESIA, 2024)
Concentration is an important ability to support the learning process and social development of children with autism. Lack of concentration often becomes an obstacle for children with autism in receiving information and interacting with the environment. Autism is a neurological and emotional disorder that affects children's communication and social interaction abilities from an early age. Children with autism often face difficulties in social interaction, including a tendency to avoid physical contact, delays in cognitive development and communication, so that children with autism have difficulty interacting with their environment. This research aims to explore the use of beaded media in training and improving concentration in children with autism. The method used involves several sessions of meronce intervention, where children are directed to arrange the beads in a specific order according to a pattern or their name. This research method uses a single case, or single subject and data collection uses observation and documentation. The results showed an increase in the subject's ability to concentrate. which is seen from longer attention duration and the ability to complete the pattern without significant assistance.